Realization of Professional Ethics among Employees of Scientific and Educational Centers (Case Study of Razi University of Kermanshah) - Mohammad Ebrahim Malmir; Ali Malmir (International Journal of Ethics and Society)
Introduction: Ethics in the work environment plays a fundamental role in the growth and development of an organization. For this reason, managers and employees should pay special attention to this issue. This is especially important in scientific and educational centers. Therefore, the purpose of this research is to investigate the level of attention paid to the various dimensions and components of professional ethics among the employees of scientific and educational centers. Material and Methods: The current research is applied and in terms of the nature of descriptive-analytical research. The statistical population included the employees of Razi University of Kermanshah, among whom 108 people were randomly selected as the research sample. The data collection tool was a questionnaire, and finally the data were analyzed using the one-sample t-test method in SPSS software. Results: After the inferential analysis, the null hypotheses were rejected and the research hypotheses were confirmed. This means that the dimensions of professional ethics were realized in Razi University and the communication dimension had the highest score and the personality dimension had the lowest score. Conclusion: Ethics in the work environment refers to the set of principles and values ​​that regulate people's behavior and working relationships and guide professional interactions. Undoubtedly, the professional ethics of employees in different dimensions of personality, social, communication and value will bring important functions such as strengthening working relationships, promoting cooperation and interaction, increasing trust and maintaining the credibility and reputation of the scientific-educational center.